¿Literatura Hispano-Filipina Contemporánea? Un ejemplo en la poesía de Edmundo Farolán Romero - Andrea Gallo (Humanities Diliman, 2007)
This paper details the results of my research on Spanish-Filipino literature through an analysis of one of its representative voices, Edmundo Farolán Romero.The Philippines has been able to absorb in a positive and constructive way the contribution of different cultural influences, which eventually became an integral part of its own culture. Some European and American cultural and linguistic elements were assimilated into a strong original Asian-Malay basis to create the modern Filipino identity. For the most part, this influence came from Spain and can be plainly seen from the interesting literary production in Spanish. This later on became the new literary voice of the Philippines from the late 18th century until the 1940s.My analysis, thus, intends to show that the literary production of Farolán Romero is a proof that the Spanish language is part of the cultural patrimony of the country. At the end of the study, I will try to analyze if the Philippines still has any trace of this rich autochthonous tradition, or if it has disappeared and just left moral and aesthetic influences in the literary production of the country.